IFN-γ-producing Th17 cells bias by HMGB1-T-bet/RUNX3 axis might contribute to progression of coronary artery atherosclerosis. Issue 2 (December 2015) - Su, Zhaoliang; Lu, Hongxiang; Jiang, Haiqiang; Zhu, Haitao; Li, Ze; Zhang, Pan; Ni, Ping; Shen, Huiling; Xu, Wenlin; Xu, Huaxi
Abstract: Background: IFN-γ-producing Th17 cells have been implicated in autoimmune disorders, but their properties in humans are known only partially. The molecular mechanisms and external factors that govern IFN-γ-producing Th17-cell bias are incompletely understood. The present work was to clarify whether (i) IFN-γ-producing Th17 cells are present in the peripheral circulation of patients with coronary atherosclerosis (CA); (ii) high mobility group box (HMGB)1 in circulation is associated with IFN-γ-producing Th17-cell bias. Methods: Thirty-six patients (17 females and 19 males; 45–84 years) diagnosed as having atherosclerosis after coronary angiography for suspected or known CA were included the study cohort. Samples of peripheral blood were collected from healthy volunteers and patients, and classical tests (flow cytometry, RT-qPCR) were used to measure blood components. Results and conclusion: Our results clearly demonstrated that HMGB1 were up-regulated in different progressive CA patients: 5.38 ± 1.48 ng/ml, 6.30 ± 1.53 ng/ml and 5.86 ± 1.12 ng/ml vs1.45 ± 0.65 ng/ml for only atherosclerotic plaque (AP), atherosclerotic plaque and some plaque rupture, no thrombosis (PR), plaque rupture and accompanying thrombosis (TH) and volunteers, respectively, p < 0.05. The frequency of IFN-γ-producing Th17 cells was 2.33 ± 0.58%, 1.93 ± 0.2% and 2.21 ± 0.65% vs 0.38 ± 0.21% for AP, PR, TH and volunteers, p < 0.05, respectively. Furthermore, HMGB1 contributed to IFN-γ-producing Th17-cell bias by controlling expression of T-bet and RUNX3. We demonstrated, for the first time, that HMGB1 is a potential inducer of IFN-γ-producing Th17-cell bias, and that IFN-γ-producing Th17 cells might be one of the pathogenic factors in atherosclerosis. Highlights: HMGB1 levels were increased in CA patients. IFN-γ-producing Th17-cells were present in the peripheral blood of CA patients. HMGB1 contributed to IFN-γ-producing Th17-cells bias by controlling expression of the transcription factors T-bet and RUNX3.